Experimental analysis of camera calibration techniques used for eye tracking - Al Kassim, Zeenat; Memon, Qurban (2015)
This paper discusses the calibration phase required prior to working of any gesture recognition or eye tracking devices. The calibration phase is an starting phase of eye tracking system. Prior to tracking phase, calibration (for eye detection) is required.Four methods have been tried in this paper, namely: using a box, multiple frames, laser and neural networks.The results of implementing each of these methods are compared to conclude the optimum solution to lead to eye detection and tracking